Research advances of Sappanone A in inflammation-related diseases - Fu, Jie; Chen, Xiu; Li, Jinglun; Peng, Lilei (Frontiers in Medicine, 2025)
Sappanone A (SA), a kind of homoisoflavanone extracted from the dry heartwood of Caesalpinia sappan L., has been shown to possess diverse bioactivities involving anti-inflammatory, antioxidant, and anti-apoptotic properties. Sustained proinflammatory state is a major factor in the occurrence and development of various diseases. Given the characteristics of SA, many studies have explored the effect of SA on inflammation-related diseases, which uncovered the multifaceted therapeutic potential of SA in such diseases. In this mini-review, we summarized the current achievements of SA on inflammation-related diseases (such as myocardial ischemia-reperfusion injury, liver injury, respiratory diseases, and kidney injury, etc.), in order to provide useful insights into the role of SA in inflammation-related diseases and benefit future clinical applications.